Correlation between Medical Record Completeness and Inpatient Length of Stay Efficiency Based on Secondary Data from Vertical Hospitals - Sri Inti; Erike Yunicha Viridula; Rini Damayanti; Alfiah Ramadhani Amran (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2025)
This study investigates the relationship between medical record completeness and inpatient Length of Stay (LOS) efficiency in Indonesian vertical hospitals managed by the Ministry of Health. Using a quantitative descriptive correlational design, data from 150 hospitals collected during 2023–2024 were analyzed. Pearson’s correlation analysis revealed a significant negative relationship (r = −0.62; p < 0.001), indicating that higher levels of medical record completeness are associated with shorter LOS. These results underscore the essential role of accurate and comprehensive documentation in improving clinical workflow, expediting decision-making, and enhancing hospital efficiency. The findings also highlight the importance of adopting Electronic Medical Records (EMR) and implementing continuous data audits to support quality improvement. Policymakers are encouraged to strengthen infrastructure, training, and digital transformation initiatives to ensure sustained improvements in national hospital performance.